A SUSTAINABLE MANAGEMENT STRATEGIES FOR SCALLOP (Amusium pleuronectes): ECOLOGICAL AND SOCIO-ECONOMIC PERSPECTIVES - Agus Kurniawan B (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2024)
The sustainability of scallop (Amusium pleuronectes) populations in South Sulawesi faces critical challenges due to habitat degradation and overexploitation. This study assesses ecological, social, and economic dimensions of scallop fisheries across five coastal regions: Pangkep, Takalar, Barru, Sinjai, and Selayar. A total of 750 scallops were sampled, and data on shell size, habitat quality, and socio-economic reliance were collected. The findings reveal a strong correlation (r = 0.82, p < 0.05) between habitat quality and scallop size, with optimal conditions in Sinjai yielding the largest scallops (mean shell length = 11 cm). Economic analysis shows that scallops contribute up to 25% of household income in certain regions, but unsustainable harvesting practices persist due to limited community awareness. This research highlights the need for ecosystem-based management, including habitat restoration, harvesting regulations, and community engagement programs. By integrating ecological and socio-economic insights, the study provides actionable recommendations for balancing conservation and livelihoods, offering a model for sustainable marine resource management.